The embodied city: Reconstructing Beirut in Zeina Abirached's A Game for Swallows. (25th January 2023) - Modarres, Andrea
In her graphic memoir, A Game for Swallows: To Die, to Leave, to Return, Zeina Abirached depicts the city of Beirut during its protracted civil war, relying on her own recollections and those of family and neighbours to reconstruct an urban environment that was radically altered by conflict. This article examines the book's depiction of Beirut as an embodied space of experience, a city that is full of life not only because of how its inhabitants adjust to the spatial disruptions of the war, but also because it lives in memory. Through both images and text, Abirached's memoir suggests that while the body of the city reflects the trauma felt by its inhabitants during conflict, it also fosters a sense of identity, illustrating that figuratively reconstructed places can serve to memorialize both individual and collective responses to trauma and its aftermath.